2017
DOI: 10.1021/acs.orglett.7b02219
|View full text |Cite
|
Sign up to set email alerts
|

Dearomatization Strategy for the Synthesis of Arylated 2H-Pyrroles and 2,3,5-Trisubstituted 1H-Pyrroles

Abstract: The first high-yielding route to arylated 2H-pyrroles was developed. The methodology utilizes 2,5-disubstituted pyrroles that are metalated, and the aryl substituents are introduced by a palladium-catalyzed cross-coupling reaction. The prepared pyrroles can be rearranged to 2,3,5-trisubstituted pyrroles under acidic conditions. Attempts to convert the 2,3,5-trisubstituted pyrroles to 2,3,4,5-tetrasubstituted pyrroles by the dearomatization rearrangement strategy were unsuccessful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 76 publications
0
33
0
Order By: Relevance
“…The lithium salt of carbazole appeared to be a better choice in comparison to the carbazole/ t BuOLi combination (Scheme D) in a Buchwald–Hartwig reaction with 1 , giving ( N -carbazolyl)­indene 7 in 73% isolated yield (Scheme E). Surprisingly, the reaction of 2,5-dimethyl-1 H -pyrrole with 1 in the presence of t BuOLi and Pd­(P t Bu 3 ) 2 gave 3- and 2-arylation products; the latter ( 18 , Chart ), containing a dearomatized 2-pyrrolyl moiety, was isolated in 57% yield. A similar reaction with 2,4-dimethyl-1 H -pyrrole gave a 1:2 mixture of N - and 2-arylated pyrroles ( 19 and 20 , Chart ; see the Supporting Information for more details).…”
Section: Resultsmentioning
confidence: 99%
“…The lithium salt of carbazole appeared to be a better choice in comparison to the carbazole/ t BuOLi combination (Scheme D) in a Buchwald–Hartwig reaction with 1 , giving ( N -carbazolyl)­indene 7 in 73% isolated yield (Scheme E). Surprisingly, the reaction of 2,5-dimethyl-1 H -pyrrole with 1 in the presence of t BuOLi and Pd­(P t Bu 3 ) 2 gave 3- and 2-arylation products; the latter ( 18 , Chart ), containing a dearomatized 2-pyrrolyl moiety, was isolated in 57% yield. A similar reaction with 2,4-dimethyl-1 H -pyrrole gave a 1:2 mixture of N - and 2-arylated pyrroles ( 19 and 20 , Chart ; see the Supporting Information for more details).…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, pyrroles can be very easily arylated at position 1 [ 14 , 15 ] or 2 [ 16 , 17 ]. In addition, the dearomatizations of pyrroles are important [ 18 , 19 , 20 , 21 , 22 ]. Similar reactivity can be expected even in the case of indole arylations.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, pyrrolidines and pyrrolines serve as vital structural cores of numerous natural products and pharmaceuticals . We envisioned that asymmetric dearomatization of pyrrole derivatives would provide an efficient and straightforward approach to diverse, highly functionalized pyrrolidines and pyrrolines. , It is particularly worth noting that in 2006, the Knochel group reported a Pd-catalyzed C–H functionalization of pyrroles, and the authors later found that a dearomatization process occurred when N -acyl-2,5-dimethylpyrrole derivatives were utilized . Inspired by this work, we recently realized a Pd-catalyzed asymmetric intramolecular dearomative Heck reaction of pyrroles employing chiral phosphine ligands.…”
mentioning
confidence: 99%